Fast and Complete Transimination of NH Imines into O‐Alkyl Oximes. Issue 4 (12th February 2015) - Jeon, Mina; Gupta, Sreya; Im, Young‐Woong; Rhee, Young Ho; Park, Jaiwook
Abstract A synthetic method for making O‐alkyl oximes was developed by combining the Ru‐catalyzed transformation of alkyl azides into NH imines and a transimination reaction with O‐alkyl hydroxylamine hydrochlorides. This process provides a wide range of O‐alkyl oximes in high yields at room temperature in short reaction times.